Spetsifika trenirovochnoi nagrzki devochek i mal'chikov v sprinterskom bege - Borek, Z. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this study was to elaborate the methodology of training means' distribution and their effect's analyses. 11 female athletes of 1, 2, 3 grades aged from 16 to 19 years acted as subjects of this research. 15 years training cycles were analyzed. The analyses of males sprinters training loads was made using the literary data. As a result of the research it was shown, that the training loads in females sprinters have the same structure as those in mal ones. It is necessary to adopt the model of training loads distribution not only to the of the given type of sport but to the functional opportunities of the growing organism of a young female athlete.